2005
DOI: 10.1039/b507496g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and “double-faced” antioxidant activity of polyhydroxylated 4-thiaflavans

Abstract: A simple synthetic methodology, based on the inverse electron demand hetero Diels-Alder reaction of electron-poor dienic o-thioquinones with electron-rich styrenes used as dienophiles, allowed the preparation of several polyhydroxylated 4-thiaflavans. Such compounds, as a function of the nature and position of the substituents on the aromatic rings, as well as of the oxidation state of the sulfur atom, are able to behave in vitro as efficient antioxidants mimicking the action of catechol containing flavonoids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 80 publications
1
42
0
1
Order By: Relevance
“…The structural modifications were inspired either by the common substitution patterns typical of the corresponding natural products or by the attempt of understanding the role played by the sulfur atom in the catechin-like and the tocopherollike antiradical performance. For this reason, 4-thiaflavane-S-oxide 3b and S,S-dioxides 2a-d were also prepared by oxidation of the corresponding sulfides with m-CPBA [12,13] (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The structural modifications were inspired either by the common substitution patterns typical of the corresponding natural products or by the attempt of understanding the role played by the sulfur atom in the catechin-like and the tocopherollike antiradical performance. For this reason, 4-thiaflavane-S-oxide 3b and S,S-dioxides 2a-d were also prepared by oxidation of the corresponding sulfides with m-CPBA [12,13] (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Initially, the ability of thiaflavanes in quenching the purple color of the commercially available 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical was expressed as SC 50 , that is, the micromolar concentration of the sample required to decrease 50% of the absorbance at 515 nm of a 100-µM solution of DPPH in methanol [13]. The double-faced ability of our compounds was verified by comparing their SC 50 with the corresponding values measured us-SCHEME 1 Synthesis of 4-thiaflavanes tested in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that these heterocycles, for their ability to act as radical scavengers, metal chelators and hydroperoxide quenchers, can be considered multi-defense antioxidants, resembling flavonoids, such as catechin, and tocopherols, the two more important families of natural polyphenolic antioxidants. [8][9][10][11][12] o-TQs were generated in situ by base-mediated elimination of phthalimide from ortho-hydroxy-N-thiophthalimides which, in turn, are the products of the S E Ar of phenols with the phthalimidesulfenyl chloride 6, PhtNSCl (Pht = phthaloyl), as reported in Scheme 1. [9,12,13] During the study of o-TQs cycloaddition reactions, we discovered that they can react as electron-poor dienes with 1,3-dienes that behave as electron-rich dienophiles.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11][12] o-TQs were generated in situ by base-mediated elimination of phthalimide from ortho-hydroxy-N-thiophthalimides which, in turn, are the products of the S E Ar of phenols with the phthalimidesulfenyl chloride 6, PhtNSCl (Pht = phthaloyl), as reported in Scheme 1. [9,12,13] During the study of o-TQs cycloaddition reactions, we discovered that they can react as electron-poor dienes with 1,3-dienes that behave as electron-rich dienophiles. This distinctive DielsAlder process occurs in any case with cyclic dienes and under thermodynamic control with acyclic derivatives.…”
Section: Resultsmentioning
confidence: 99%